Cooperative spectrum sensing scheduling scheme based on discrete particle swarm optimization algorithm - Xing ZHANG; Ye WANG; Yi YANG; Qin-yu ZHANG (Tongxin xuebao)
The statistical characteristics of the network state changes were analyzed by using the CTMC model.Considering the difference of each secondary user’s sensing ability,two integer programming problems on cooperative sensing scheduling scheme were established from two aspects:the primary users and the secondary users respectively.A discrete particle swarm optimization algorithm was proposed to solve the integer programming problems,and compared with the traditional random scheduling scheme and greedy scheduling scheme based on SNR.The simulation results show that the cooperative sensing scheduling scheme based on discrete particle swarm optimization algorithm is superior to random scheduling scheme and greedy scheduling scheme based on the SNR,which gets a higher spectrum sensing accuracy.